(−)-Epicatechin mitigates radiation-induced intestinal injury and promotes intestinal regeneration via suppressing oxidative stress. (3rd August 2019) - Li, Ya; Ma, Shanshan; Zhang, Yanting; Yao, Minghao; Zhu, Xiangzhan; Guan, Fangxia
Abstract: The high radiosensitivity of the intestinal epithelium limits the survival of victims by nuclear accidents or terrorism and limits effective radiotherapy against abdominal malignancies. Recently, we reported that (−)-epicatechin (EC) modulates oxidative stress and exerts neuroprotection. Here, we investigate the protective effects of EC against intestinal damage induced by radiation. The established model is acute moderate but reversible intestinal injury damage. We also set up the injured model of "minigut" ex vivo, which mimic the process of intestinal regeneration in vivo . We found that EC can repress oxidative stress by regulating SOD and MDA levels in serum and intestine tissue. Correspondingly, EC can decrease apoptosis of crypt cells in Lgr5-EGFP-IRES-creERT2 mice after radiation. Further studies demonstrated that EC can promote Nrf2 translocation from cytoplasm to nuclear and then activate the expression of HO1 and NQO1. Interestingly, EC can enhance the activity of intestine stem cells labelled by Lgr5 and promote intestinal epithelium regeneration determined by HE and immunofluorescence staining in vivo and in vitro . We also found that EC can activate the Wnt/β-catenin signal pathway confirmed by TCF/LEF luciferase reporter assay. Together, EC can provide the protective effect on intestine and promote intestinal regeneration after radiation through Nrf2 and Wnt/β-catenin signal pathway.